Tretí sektor a dobrovoľníctvo - Španková, Jana; Grenčíková, Adriana (Univerzita Pardubice, 2012)
This contribution deals with development, merit and responsibility of nongovernmental organizations in the Slovak republic. In addition the possible trends and the line of further development of this sector are mentioned.
The third sector and volunteering
Keywords: third sector; non-governmental organizations; financing; trends; vision